Evaluating Company’s Readiness for Adopting Product Line Engineering: a Second Evaluation Round - Luisa Rincón; Raúl Mazo; Camille Salinesi (Complex Systems Informatics and Modeling Quarterly)
Product lines have emerged in the software industry as an attractive approach to perform planned reuse of code. Nevertheless, a product line solution is not appropriate in all cases and also requires some conditions to be implemented successfully. The literature offers several contributions regarding the adoption of product lines. However, only a few of them are able to support decision-makers in making informed decisions in favor of or against following this approach. We proposed APPLIES, a framework for evaluating the organization’s motivation and preparation for adopting product lines. This article presents the second version of the APPLIES framework as well as the second iteration of the evaluation of this approach. This evaluation consisted of (i) a workshop with a practitioner who had experience in adopting the product line production approach and; (ii) a review of the content by five product line experts. The results obtained from the evaluation resulted in modifications to the framework content, mainly to simplify the statements and eliminate redundant elements. Also, we detected new functionalities and modifications that we expect to be resolved in the following evaluation iterations. Further evaluations and improvements are needed to mature the framework. Moreover, we expect to incorporate APPLIES into a process that covers the aspects that a company must consider before deciding to adopt this production paradigm.